Advancements and trends in digestive system autotransplantation: a bibliometric and visualization analysis - Aimitaji Abulaiti; Talaiti Tuergan; Talaiti Tuergan; Alimu Tulahong; Alimu Tulahong; Ruiqing Zhang; Ruiqing Zhang; Yingmei Shao; Yingmei Shao; Yingmei Shao; Tuerganaili Aji; Tuerganaili Aji (Frontiers in Medicine, 2025)
BackgroundDigestive system autotransplantation is an emerging surgical technique used to treat complex digestive diseases.MethodsThis study conducted a bibliometric analysis of 748 publications from the Web of Science Core Collection (WoSCC) database, using VOSviewer and CiteSpace tools to map research trends, author contributions, and institutional collaborations. Articles were selected based on their relevance to digestive system autotransplantation, focusing on autologous liver, pancreatic, and small intestine transplantation. The analysis included publication volume, citation counts, key authors, leading journals, and keyword co-occurrence.ResultsThe analysis revealed a steady rise in publications between 2004 and 2015, followed by a gradual decline after 2016. The United States leads in research output, accounting for 40.11% of publications, followed by China. The leading institutions are predominantly based in the United States, with the University of Minnesota System producing the most publications. High-frequency keywords include autologous transplantation, pancreatic transplantation, chronic pancreatitis (CP), and postoperative complications.ConclusionDigestive system autotransplantation is a promising approach for complex cases. Continued interdisciplinary collaboration and focus on clinical outcomes will drive future advancements.